2020
DOI: 10.1038/s41564-019-0640-1
|View full text |Cite
|
Sign up to set email alerts
|

Commensal Bacteroidetes protect against Klebsiella pneumoniae colonization and transmission through IL-36 signalling

Abstract: The microbiota primes immune defences but the identity of specific commensal microbes which protect against infection is unclear. Conversely, how pathogens compete with the microbiota to establish their host niche is also poorly understood. Here, we investigate the antagonism between the microbiota and Klebsiella pneumoniae during colonization and transmission. We discover that maturation of the microbiota drives the development of distinct immune defence programs in the upper airway and intestine to limit K. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(82 citation statements)
references
References 49 publications
1
75
0
Order By: Relevance
“…Klebsiella pneumoniae disease manifestations in the respiratory and urinary tract have been extensively modeled in animals (4). However, the gastrointestinal mucosal surface, also colonized readily by Kpn has not been the focus of many scientific studies (51, 52). In this report, we describe a murine model of oral infection of K. pneumoniae to study GI colonization and host-to-host transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Klebsiella pneumoniae disease manifestations in the respiratory and urinary tract have been extensively modeled in animals (4). However, the gastrointestinal mucosal surface, also colonized readily by Kpn has not been the focus of many scientific studies (51, 52). In this report, we describe a murine model of oral infection of K. pneumoniae to study GI colonization and host-to-host transmission.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, we observed that the APACHE II score (p < 0.001) and SOFA score (p < 0.001) were higher in the death group. In the death group, the hospitalization days before BSI were relatively longer (8 [4,18] days versus 14 [5,22] days, p = 0.015).…”
Section: Risk Factors For Death In Patients With Klebsiella Pneumoniamentioning
confidence: 96%
“…These facultative anaerobic bacteria have low nutritional requirements, no flagella, no spores, an obvious capsule, and strong resistance to the outside world. Klebsiella pneumoniae can colonize in the respiratory tract and skin, as well as become aerosolized (3)(4)(5). There are a variety of clinical manifestations, including bloodstream infection (BSI), pulmonary infection, urinary tract infection, abdominal infection, and so forth (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…the LCN2 and reg3 family), IEC proliferation and mucins suggests that it may have direct/indirect effects on the composition of the microbiota. 10,14,16,76 IL-36R signalling has also been shown to alter the microbiota composition and protect mice from obesity. 10 The altered microbiota in genetically modified mice lacking IL-36R could potentially influence defective recovery following DSS-mediated acute intestinal inflammation.…”
Section: What Is the Relationship Between Il-36 And The Microbiota?mentioning
confidence: 99%